(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
ABSTRACT Â A newÂ polymer surfactant derived from cis-1,4-cyclohexane bis(methylamine) and ethylenediamintetraacetic acid [2,2’-(1,12-bis(4-(aminomethyl)cyclohexyl)-3,10-dioxo-2,5,8,11-tetraazadodecane-5,8-diyl) diacetic acid ] was synthesized and characterized by FTIR and 1HNMR. A series of electrochemical measurements, including corrosion potential and corrosion current has been made on the surfactant for Â carbon steel samples in corrosiveÂ environment. Results showed that the surfactant Â can offer some degrees of protection in the corrosive environments. The corrosion study of this polymer outline thatÂ it haveÂ a good resistant to the corrosion of carbon steel in 0.1 M solution of HCl, which can be indicate to Â uses as anti-corrosion materials